Biomechanics of Ankle Sprains: A 3D Dynamic Analysis of Lateral Tensile Load. Issue 1 (January 2022) - Lintz, Francois; Netto, Cesar de Cesar; Dufrénot, Maryama S.; Lalevée, Matthieu; Lopes, Ronny; Fernando, Céline; Bernasconi, Alessio
Category: Ankle; Sports Introduction/Purpose: Lateral ankle sprains are the most frequent ankle trauma and may lead to chronic lateral ankle instability (CLAI). Studies have reported anterior talofibular (ATFL) and calcaneofibular (CFL) ligaments tensile strengths around 200N and 300N. Cone Beam Weight Bearing CT (WBCT) allows visualization of 3D bony anatomy in different functional positions. The primary objective of this study was to calculate 3D ATFL and CFL tensile loads in patients diagnosed with CLAI performing Forced Inversion stance during WBCT imaging (FI-WBCT) and wearing shoes, and to compare them with a population of non-CLAI ankles. The secondary objective was to evaluate the relative contribution of shoes. We hypothesized that ATFL and CFL calculated tensile loads (CTLs) would be close to previously published data with minimal contribution of shoes. Methods: This retrospective comparative Level III study included 20 CLAI ankles and 20 controls with known demographics and available FI-WBCT datasets. Patients under 18 or with a previous history of trauma or surgery which could affect ankle architecture were excluded. A mechanical lever arm model was calculated for each case using the spatial coordinates of the weight bearing surfaces of the shoe and foot (bony landmarks: 5th metatarsal head, base and calcaneus lowest points, distal tip of the medial malleolus, ATFL and CFL distal insertion points, distal tip of the fibula). The ATFL and CFL CTL were calculated respectively as the coronal force applied at the distal insertion landmarks of the ATFL on the talus and CFL on the calcaneus. Normality was assessed using the Shapiro-Wilk test, then variables were compared using the Student t-test (normally-distributed) or the Wilcoxon rank sum test (non normally-distributed variables). Chi-2 was used for categorical variables. Results: Mean age [42.4+-10.9 vs 40.8+-10.7 years; p=0.317], Body Mass Index [24.4+-3.3 vs 24.9+-4 kg.m-2; p=0.34], sex (p=0.75), side (p=0.75) and foot alignment (FAO -1.05%+-5.5 vs 0.08%+-3.6; p=0.22) were not different between CLAI ankles and controls. CTLs for ATFL were 194N+-149 in CLAI and 192N+-183 in controls (p=0.85), while for CFL they were 311N+-286 and 311N+-361, respectively (p=0.79). Using footwears, CTLs were 406N+-360 in CLAI vs 608N+-380 in controls (p<0.05) for ATFL, and 703N+-741 vs 958N+-779 (p=0.11) for CFL. Comparing barefoot and shod values, mean CTLs in the ATFL (193N+-164.8 vs 507N+-379.1, respectively; p<0.001) and in CFL (311.3N+-321 vs 830.8N+-761.5, respectively; p<0.001) were significantly different. Conclusion: We found that the Calculated Tensile Loads for ATFL and CFL using Forced Inversion-WBCT considering the barefoot weightbearing surface were close to values described in previous cadaveric studies for those ligaments' tensile strength. A 2.6 and 2.7 fold increase was found when the weight bearing surface of the shoe was considered, indicating a possible aggravating role of shoewear. The reduced shod ATFL-CTL values found in unstable cases as compared to controls could suggest a possible active self-protection mechanism during FI-WBCT in CLAI.